Development of para rubber seed oil as the efficient makeup remover - Nattaya Lourith; Mayuree Kanlayavattanakul (Universidade de São Paulo, 2020)
The para rubber tree (Hevea basilensis) is an economically important tropical tree species that produces natural rubber, a valuable industrial raw material. Innovative products that are derived from by-products from the rubber production process, such as seeds, are important for the sustainability of the para rubber industry. Therefore we subjectively assessed para rubber seed oil for its makeup-removal efficacy and developed it into a makeup cleansing product with appropriate quality control measures for the cosmetic industry. The makeup-removal efficacy of para rubber seed oil was analyzed using a validated UV-Vis spectroscopy, which indicated that the oil removed 86.21 ± 2.48% of liquid foundation [relative standard deviation (RSD) = 2.88%]. Therefore, we developed stable makeup removers containing 40-70% para rubber seed oil. Bio-oil removers containing 50% and 60% oil had the best appearance and texture and were subsequently evaluated for their makeup-removal efficacy. The bio-oil remover with the higher oil content was significantly better at removing makeup (95.26 ± 0.97% removal by the 60% oil compared with 73.88 ± 3.97% removal by the 50% oil). To conclude, para rubber seed oil is a promising new bio-oil for the cosmetic industry, which broadens consumers' choices of bio-oil makeup removers. We believe that the manufacture and quality control of this innovative and efficient makeup remover are feasible on an industrial scale.